1990
DOI: 10.1288/00005537-199006000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus dna in laryngeal squamous cell carcinomas by polymerase chain reaction

Abstract: The presence of human papillomavirus genomes-16 and -6b in metastatic cervical lymph nodes was examined in 34 cases of laryngeal carcinomas by means of polymerase chain reaction, which had been fixed in formalin and embedded in paraffin. Human papillomavirus DNAs extracted from paraffin-embedded tumor tissues were used for polymerase chain reaction with amplification of the E6 region of human papillomavirus genome-16 and the E1 region of human papillomavirus genome-6b. Human papillomavirus genome-16 sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 16 publications
4
32
2
3
Order By: Relevance
“…A link between HPV infection and cervical cancer has been demonstrated in over 99% of specimens (Walboomers et al, 1999). Recent investigations, on the other hand, do not support HPV as an important factor in the pathogenesis of laryngeal epithelial lesions (Brandwein et al, 1993), although the prevalence of HPV in laryngeal carcinomas has been found to range from 5 to 54.1% (Hoshikawa et al, 1990;Perez-Ayala et al, 1990;Brandwein et al, 1993). The aetiology of laryngeal cancer is more likely to be related to cigarette smoking, alcohol abuse and exposure to other extrinsic irritants.…”
Section: Discussionmentioning
confidence: 99%
“…A link between HPV infection and cervical cancer has been demonstrated in over 99% of specimens (Walboomers et al, 1999). Recent investigations, on the other hand, do not support HPV as an important factor in the pathogenesis of laryngeal epithelial lesions (Brandwein et al, 1993), although the prevalence of HPV in laryngeal carcinomas has been found to range from 5 to 54.1% (Hoshikawa et al, 1990;Perez-Ayala et al, 1990;Brandwein et al, 1993). The aetiology of laryngeal cancer is more likely to be related to cigarette smoking, alcohol abuse and exposure to other extrinsic irritants.…”
Section: Discussionmentioning
confidence: 99%
“…Cerca de 40% dos carcinomas espinocelulares invasivos de laringe apresentam o tipo 16 do HPV 27 . Não se pode, contudo, afirmar que a transformação maligna na papilomatose ocorre exclusivamente associada à presença do HPV, ou se trata-se de um fenômeno paralelo associado a outros estímulos carcinógenos a que a laringe está exposta.. Co-fatores capazes de modificar genes celulares e/ou controladores intracelulares como álcool, tabaco, Vírus Herpes Simplex e Citomegalovírus podem agir como iniciadores responsáveis pela oncogênese 8,28,29 .…”
Section: Discussionunclassified
“…Very rarely, squamous cell carcinomas can arise in pre-existing laryngeal papillomas after a long latency period. Surprisingly, most of the HPV-positive laryngeal carcinomas contain HPV-16 (Hoshikawa et al, 1990;Perez-Ayala et al, 1990;McCuUough & McNicol, 1991), but the malignant progression of laryngopharyngeal lesions containing HPV-6 or-11 has also been reported (Zarod et al, 1988;Lindeberg et al, 1989). However, duplications and insertions are often found in the upstream regulatory region (URR) of low-risk HPVs present in high-grade lesions (Boshart & zur Hausen, 1986;Rando et al, 1986a;Kasher & Roman, 1988;DiLorenzo et al, 1992).…”
Section: Discussionmentioning
confidence: 99%